Photoconduction Properties in Tungsten Disulfide Nanostructures - Hemanth Kumar Bangolla; Yueh-Chien Lee; Wei-Chu Shen; Rajesh Kumar Ulaganathan; Raman Sankar; He-Yun Du; Ruei-San Chen (Nanomaterials, 2023)
We reported the photoconduction properties of tungsten disulfide (WS2) nanoflakes obtained by the mechanical exfoliation method. The photocurrent measurements were carried out using a 532 nm laser source with different illumination powers. The results reveal a linear dependence of photocurrent on the excitation power, and the photoresponsivity shows an independent behavior at higher light intensities (400–4000 Wm−2). The WS2 photodetector exhibits superior performance with responsivity in the range of 36–73 AW−1 and a normalized gain in the range of 3.5–7.3 10−6 cm2V−1 at a lower bias voltage of 1 V. The admirable photoresponse at different light intensities suggests that WS2 nanostructures are of potential as a building block for novel optoelectronic device applications.